Prolifération de Cissus quadrangularis L. dans le Parc National des Iles-de-la-Madeleine, Sénégal - Ephrem Nzengue; Bienvenu Sambou; Abou Thiam; Kandioura Noba; Yacinthe Sambou; Jacques François Mavoungou (VertigO, 2016)
National parks are representative protected areas of natural ecosystems of a country. The introduction of alien plants in natural systems present a risk to biodiversity conservation, particularly where protected areas are islands. In the past few years , Cissus quadrangularis, a plant species from Indo-Malaysian, introduced in Senegal around 19th century, has developed signs that warry the authorities of Madeleine Islands National Park (MINP) of over 45 hectares. The present work was undertaken to evaluate the status on the distribution of C. quadrangularis and provide the information on the impact of that species on the ecosystems in this country part. The phytosociological surveys highlighted eight plant communities. From digital image (Quickbird) of 1 meter resolution, the main facies of occupancy were mapped and the areas occupied by C. quadrangularis were estimated. The surface of occurrency (5.7 ha) of plant stands population represent 27.2 % of the total area of the islands (20.9 ha). This plant is threats to biodiversity of the Park. It is urgent to find and implement appropriate measures to control the spread of the plant in the park.